Ultrasonic-Assisted Transesterification of Tripalmitin Using Limestone-Derived CaO Catalyst - Rakhma Amalia Nurdina; Yuichi Kamiya; Adhi Dwi Hatmanto; Fajar Inggit Pambudi; Suyanta Suyanta; Nuryono Nuryono (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
In producing palm oil-based biodiesel (fatty acid methyl esters) through the transesterification of triglycerides with methanol, a high-performance and straightforward catalyst is required. This research studies the synthesis and characterization of limestone-derived calcium oxide as a heterogeneous base catalyst for the transesterification of tripalmitin, a representation of palm oil triglycerides, with methanol to produce methyl palmitate. Limestone was calcined at 800 °C to produce CaO. The resulting catalyst was characterized using TGA, XRD, FTIR, SAA, and CO2-TPD. The catalytic performance was compared with that of commercial calcium oxide under optimal reaction conditions, namely 50 °C temperature, 60 min reaction time, and 30 mg catalyst mass. The results showed that limestone-derived CaO produced a higher yield (44.6%) than commercial CaO (32.3%). The kinetics study showed that the reaction followed a two-order pseudo-kinetic model with a reaction rate constant value of 0.1450 L mmol-1 min-1. Overall, limestone-derived CaO proved to be an effective, inexpensive, and environmentally friendly alternative catalyst in the production of triglyceride-based biodiesel. Furthermore, the modification of CaO to enhance the catalytic activity needs to be explored further. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).